2013
DOI: 10.4314/ahs.v13i1.21
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of cholelithiasis in Sudanese children with Sickle Cell Anaemia (SCA) after 13 years follow-up

Abstract: Background: SCA causes chronic haemolysis which is a risk factor for cholelithiasis. Objective: To determine the prevalence and outcome of children with SCA complicated with gallstones treated at the sickle cell clinic at the children emergency hospital Khartoum state. Methods: 261 patients age 4 months to 16 years were studied. AUS examination was carried out. The 30 patients in whom gall stones were detected followed prospectively from June 1996 to September 2009 when a second AUS examination was obtained.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
27
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(45 citation statements)
references
References 33 publications
8
27
0
2
Order By: Relevance
“…Other authors as Silva in Greece and Itoua in Nigeria [10] [11] reported a prevalence greatly superior to ours, 40.9% and 31.30% respectively. However, many other African studies reported lower prevalence: 9.3% in Côte d'Ivoire, 9.4% in Senegal and 11.5% in Sudan [1] [2] [12]. Differences observed between prevalences could be related to patients' age in the series, their mode of selection or clinical signs.…”
Section: Prevalence Of Cholelithiaismentioning
confidence: 81%
See 4 more Smart Citations
“…Other authors as Silva in Greece and Itoua in Nigeria [10] [11] reported a prevalence greatly superior to ours, 40.9% and 31.30% respectively. However, many other African studies reported lower prevalence: 9.3% in Côte d'Ivoire, 9.4% in Senegal and 11.5% in Sudan [1] [2] [12]. Differences observed between prevalences could be related to patients' age in the series, their mode of selection or clinical signs.…”
Section: Prevalence Of Cholelithiaismentioning
confidence: 81%
“…Sickle cell disease is a genetic disease that causes anemia as well as acute and chronic tissue injuries in many organs [1]. Providing better care in our unit has increased the life expectancy of children with SCD [8].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations